Logistics Management Model to reduce non-conforming orders through Lean Warehouse and JIT: A case of study in textile SMEs in Peru - Coronel Vasquez, Jose Renato (2023)
The company chosen for this case of study was a textile SME that represents qualitatively and quantitatively the sector. This allows us to measure the impact on the economic retribution and costs incurred by inappropriate supply management. The research aims to optimize this supply management through an improved model based mainly on Lean Warehouse and JIT. Successful cases of applying the different Lean techniques guarantee improvements in process efficiency, resulting in cost reduction [8]. Although there are scientific articles that implement Lean tools to improve supply problems, the innovation of the article lies in the implementation of Lean Warehouse and Just-in-Time simultaneously, adding 5S tools. Furthermore, the application of a supplier assessment to support the new methodology implemented in the company.